2014
DOI: 10.3389/fnagi.2014.00143
|View full text |Cite
|
Sign up to set email alerts
|

Copper: from neurotransmission to neuroproteostasis

Abstract: Copper is critical for the Central Nervous System (CNS) development and function. In particular, different studies have shown the effect of copper at brain synapses, where it inhibits Long Term Potentation (LTP) and receptor pharmacology. Paradoxically, according to recent studies copper is required for a normal LTP response. Copper is released at the synaptic cleft, where it blocks glutamate receptors, which explain its blocking effects on excitatory neurotransmission. Our results indicate that copper also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 73 publications
(87 reference statements)
0
91
0
Order By: Relevance
“…Decreased FA in a number of tracts has been shown to be a marker of AD dementia, relating changes in diffusive properties of white matter to impairment in AD dementia [20]. FA has been shown to be less sensitive to the early changes of mild cognitive impairment [21]; however, the significant differences that we found in FA between those with high and executive abilities suggests that FA changes in MCI may be related to executive deficits [22]. Our study confirms that the white matter changes found previously in AD may manifest earlier as a function of diminished executive abilities in MCI, and that these diminished abilities are likely to accompany early white matter changes in specific white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FA in a number of tracts has been shown to be a marker of AD dementia, relating changes in diffusive properties of white matter to impairment in AD dementia [20]. FA has been shown to be less sensitive to the early changes of mild cognitive impairment [21]; however, the significant differences that we found in FA between those with high and executive abilities suggests that FA changes in MCI may be related to executive deficits [22]. Our study confirms that the white matter changes found previously in AD may manifest earlier as a function of diminished executive abilities in MCI, and that these diminished abilities are likely to accompany early white matter changes in specific white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Several new therapeutic strategies are currently aimed at regulating and restoring metal homeostasis (Opazo et al, 2014; Bharti et al, 2016). Interestingly, also four neurotrophic factor, namely BDNF, CNTF, PEDF, GDNF, have been reported to increase the intracellular Zn level in RPE (retinal pigmental epithelium) cells, modulating the expression of zinc transporters which increase zinc uptake (Leung et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For detailed discussions of the role of copper in neurobiology, the reader is referred to recent reviews by D'Ambrossi and Rossi (55), Gaier, Eipper and Mains (56), and Opazo, Greenough and Bush (57). While neurobiology has long hinted at the prospects of copper signaling, the identification and study of copper signaling in other tissues with more detailed study of specific molecular targets is rapidly expanding.…”
Section: Copper Signaling In Neurobiologymentioning
confidence: 99%